Unleashing the Power of Marketing Management to Boost School Enrollment Excitement - Paluru, Muh. Chaidir; Said, Rukman AR; Bulu, Bulu (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2024)
This research examines educational marketing management strategies to enhance student enrollment interest at SDIT Harith Foundation in Palopo City. It focuses on three primary objectives: 1) Describing the strategies used to increase student enrollment interest, 2) Identifying challenges encountered by the educational marketing management team in achieving this goal, and 3) Outlining the solutions employed to overcome these challenges. The research uses a qualitative approach with a descriptive methodology. The subjects include the school principal, teachers, staff, and parents of prospective students at SDIT Harith Foundation in Palopo City. Data collection methods involve interviews and document analysis, with data processing through reduction, presentation, and verification. Findings from the study are as follows: 1) SDIT Harith Foundation implements a range of comprehensive strategies to boost student enrollment interest. These include market segmentation, brand development, communication and promotional tactics, stakeholder engagement, product adjustment, market research, pricing, distribution, and feedback analysis; 2) Despite these efforts, the school faces challenges such as competition with other educational institutions, varied learning styles among students, coordination among departments, and the need for clear communication with parents; 3) To address these challenges, the school has adopted various solutions. These include curriculum innovation, facility improvements, personalized learning, enhanced inter-departmental coordination, and transparent communication with parents to build trust. These strategies and solutions have proven effective in boosting enrollment interest and highlighting areas for ongoing improvement.